Of Mad Cows and Dead Pigs: Negotiating Food Safety and Everyday Sovereignty in Taiwan. Issue 5 (20th October 2022) - Yuen, Samson; Kan, Karita
ABSTRACT: The globalisation of food and agricultural trade has brought issues of food safety and biosecurity to the centre of geopolitical research. This paper explores the relationship between food risks and sovereignty practices, a topic that has received relatively scant attention in the scholarship. Going beyond conventional conceptualisations of sovereignty as an external-legal notion that is delimited to the realm of 'high politics' in international relations, this paper points to how it is also expressed and negotiated in quotidian practices of food import and consumption, and how this has contributed to the politicisation of food safety. Focusing on the case of Taiwan, a de facto island state with contested sovereignty status, and comparing the food safety discourses that arose during the outbreaks of Mad Cow Disease and African Swine Fever, we argue that food risks provide opportunities for social and political actors to participate in the everyday construction of sovereignty. While the Taiwanese government's handling of the Mad Cow Disease shows it to be ultimately constrained by the geopolitical reality of fragile sovereignty, the outbreak of African Swine Fever enabled it to legitimise the securitisation of borders and bolster its legitimacy by staging collective defensive actions against perceived external risks. By drawing attention to how sovereignty is produced and performed through practice, this paper further advances recent discussions of sovereignty as a dynamic, social process.